Anodic oxidation-assisted O2 oxidation of phenol catalyzed by Fe3O4 at low voltage. (20th January 2018) - Lei, Lei; Fang, Li-Ming; Zhai, Lin-Feng; Wang, Ran; Sun, Min
Abstract: Environmentally friendly and economically feasible technology is urgently needed for the management of phenolic compounds. Here, low-voltage degradation of phenol is achieved in an anodic oxidation (AO)-assisted O2 oxidation process with Fe3 O4 /graphite felt (GF) composite anode. Batch experiments on phenol degradation at 0.6 V achieve phenol removal in 78 h, and the total mineralization of phenol is obtained in 90 h at the first cycle. The time required for phenol removal is reduced to 48 h after three cycles of operation, meanwhile mineralization of phenol being completed in 51 h. The AO-assisted O2 oxidation process is confirmed to adopt a non-radical pathway in which the phenol is degraded at the catalytic sites of GF under the synergy of O2 and anodic electric field. Phenol degradation efficiency at the Fe3 O4 /GF composite anode is significantly higher than that at the GF, which is ascribed to the accelerated electron transfer by Fe3 O4 . The FeC and FeOC bonds are identified as inherent linkages responsible for electron transfer between the Fe3 O4 and GF. Process efficiency is able to be spontaneously enhanced in recycling operation due to the intensification of FeC and FeOC bonds. The low energy cost and application of cheap carbonaceous anode endow the AO-assisted O2 oxidation process with great potential for use in the remediation of phenol pollutant. Graphical abstract: Image 1 Highlights: Phenol is degraded by AO-assisted O2 oxidation with Fe3 O4 /GF anode at 0.6 V. Electron transfer from phenol to O2 is catalyzed by functional groups on GF. Fe3 O4 in Fe3 O4 /GF composite enhances electron transfer during process. FeC and FeOC bonds enable electron transfer between Fe3 O4 and GF. Spontaneously improved process efficiency due to intensified FeC and FeOC bonds.